Enhancing Operational Performance through Green Manufacturing Practices: Case Studies from TQM Implementation in the Indonesian Industrial Sector - Soesilo, Rahman (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Enhancing Operational Performance through Green Manufacturing Practices: Case Studies from TQM Implementation in the Indonesian Industrial Sector. This study explores the impact of environmentally friendly manufacturing practices on the performance of the Indonesian industrial sector, with a specific focus on Total Quality Management (TQM) implementation. The research aims to evaluate the application of green manufacturing, examine its effects on operational parameters, identify key success factors, and provide strategic recommendations. A mixed-methods approach, comprising surveys, interviews, and case studies, was employed to gather quantitative and qualitative data from various industries in Indonesia. The results of the study indicate a positive correlation between green manufacturing practices and performance indicators. High-performing companies achieved cost savings, resource optimization, and greater energy efficiency. Success factors included employee involvement, technology adoption, and regulatory compliance. In conclusion, integrating green manufacturing within the TQM framework is crucial for sustainable industrial development. The study emphasizes the need for proactive and collaborative decommissioning strategies and continuous improvement cycles.